THE STUDY OF SOCIAL WELL-BEING ON THE EXAMPLE OF “VELVET” REVOLUTION - Ghazaryan , I. A.; Margaryan, A. (Modern Psychology, 2019)
The purpose of this article is to subject the concept of social well-being to theoretical and empirical analysis. The authors will present a study of changes in social well-being on the example of the “velvet revolution” that occurred in Armenia in 2018. The authors linked the levels of social well-being with the value orientations of the individual.
Keywords: social well-being, values, “velvet” revolution.